2015
DOI: 10.3889/oamjms.2015.037
|View full text |Cite
|
Sign up to set email alerts
|

Prelabour Rupture of Membranes: Mode of Delivery and Outcome

Abstract: BACKGROUND:Pre-labour Rupture of Membranes (PROM) is an important cause of maternal and fetal morbidity and increased rate of cesarean section delivery.AIM:The aim of this study is to investigate the clinical characteristics, PROM-delivery interval, mode of delivery, and early maternal neonatal outcome among pregnant patients presenting with pre-labour rupture of membranes.MATERIAL AND METHODS:This prospective case control study is implemented at the Obstetric and Gynecology Clinic of the University Clinical C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 8 publications
(6 reference statements)
2
13
1
1
Order By: Relevance
“…Our data showed that premature rupture of membrane and intrauterine growth retardation were common among primigravida with significant statistical difference as it was showed in this study which among 100 pregnant with premature rupture of membrane 63 were primigravida ( 16 ).…”
Section: Discussionsupporting
confidence: 61%
“…Our data showed that premature rupture of membrane and intrauterine growth retardation were common among primigravida with significant statistical difference as it was showed in this study which among 100 pregnant with premature rupture of membrane 63 were primigravida ( 16 ).…”
Section: Discussionsupporting
confidence: 61%
“…Tahir et al had a caesarean section proportion in PROM of 14%[ 6 ]. Eleje reported a caesarean section proportion of 23% while Ibishi et al reported one of 28%[ 7 , 8 ]. Other studies however had higher cesarean proportions: Tavassoli et al reported a caesarean section proportion in PROM of 32%[ 12 ], while Pasquier et al reported a caesarean section rate of 58.7%[ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although caesarean delivery is often recommended, there is no consensus on the ideal delivery mode in PROM in resource limited settings [ 4 – 8 ]. Management of PROM is particularly challenging in low-resource settings, where access to caesarean delivery may be limited and may result in long waiting times for surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors are involved in the incidence of IVH, the most important of which include respiratory distress, hypoxiainduced damage, ischemia, high or low blood pressure, increased venous blood pressure, pneumothorax, and hypovolemia [ 3 ]. Symptoms of IVH are nonspecific and differ according to the severity of the disease [ 4 ].…”
Section: Introductionmentioning
confidence: 99%